Physiological effects of water deficit on two oil palm (Elaeis guineensis Jacq.) genotypes (2015)
Water supply is the main limiting factor that affects oil palm (Elaeis guineensis Jacq.) yield. This study aimed to evaluate the gas exchange and photosynthetic capacity, determine the physiological effects and assess the tolerance potential of oil palm genotypes under water-deficit conditions. The two oil palm commercial genotypes IRHO1001 and IRHO7010 were exposed to soil water potentials of -0.042 MPa (field capacity or well-watered) or -1.5 MPa (drought-stressed). The leaf water potential and gas exchange parameters, including photosynthesis, stomatal conductance, transpiration and water use efficiency (WUE), as well as the photosynthesis reduction rate were monitored at 4 and 8 weeks after treatment. The IRHO7010 genotype showed fewer photosynthesis changes and a smaller photosynthetic reduction under the prolonged water deficit conditions of 23% at 4 weeks after the treatment as compared to 53% at 8 weeks after treatment, but the IRHO1001 genotype showed 46% and 74% reduction at the two sampling times. ‘IRHO7010’ had a higher stomatal conductance and transpiration potential than ‘IRHO1001’ during the water shortage. The WUE and leaf water potential were not different between the genotypes during dehydration. The data suggested that ‘IRHO7010’ had a higher photosynthetic capacity during the drought stress and was more drought-tolerant than ‘IRHO1001’.